Kuwait : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
This Financial System Stability Assessment paper discusses that Kuwait's limited economic diversification is directly reflected in the bank-centric financial sector. Banks have high concentrations to single borrowers, large depositors, and sectors, as well as significant common exposures. Risks to the financial sector are mostly external, stemming from oil price shocks, geopolitical tensions, and global financial developments. The risks are mitigated by sizeable sovereign financial assets, and by the ability of public entities to provide liquidity through large deposits. Stress tests suggest that banks are resilient to a wide range of shocks. The newly developed regulatory framework for capital market participants and products is an important step, but some gaps remain. The authorities have made important progress in strengthening the macroprudential framework. The crisis management framework and financial safety net arrangements should be strengthened and further operationalized. The diversification and resilience of the economy is expected to benefit from better financial inclusion of small-and-medium enterprises.